2010
DOI: 10.1111/j.1755-6686.2010.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

One Unit's Experiences When Establishing Buttonhole Technique, Analysis of Reasons for Failure of Procedure: A Report

Abstract: The buttonhole technique of access of needle insertion into a single selected site in the arteriovenous fistula has proved to be a reliable alternative to older methods due to its overall low complication rates. Although the use of blunt needles improves the technique, the success rate of cannulation with these needles is difficult to predict. We analysed the short-term outcome of 16 patients receiving in-centre haemodialysis and compared clinical relevant parameters between patients with and without buttonhol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…However, it is rewarding to see that buttonhole sites are ‘seeing the test of time’ and that they have not failed as they have in other units (Galante et al . ). The Renal Service considers that the reported extra costs associated with buttonhole cannulation supplies (Ludlow ) are minimal compared to the cost of a central line necessitated by a traumatic cannulation with the rope‐ladder technique.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is rewarding to see that buttonhole sites are ‘seeing the test of time’ and that they have not failed as they have in other units (Galante et al . ). The Renal Service considers that the reported extra costs associated with buttonhole cannulation supplies (Ludlow ) are minimal compared to the cost of a central line necessitated by a traumatic cannulation with the rope‐ladder technique.…”
Section: Discussionmentioning
confidence: 97%
“…; Galante et al . ), although there are some suggestions that buttonhole cannulation could perhaps become the default technique (Murcutt ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In our recently published experience (Galante et al 3 ), the buttonhole technique showed to be a useful and efficient method, which, in theory, could be routinely used in all patients. Its main advantages are the possibility of using short-trajectory fistulas, the absence of aneurysm formation, decrease in painful sensations during punctures, prolonging the fistula service life and decreasing bleeding and hematomas, improving the esthetical aspect.…”
Section: Lead Us To Two Types Of Commentsmentioning
confidence: 97%
“…Studies were excluded for the following reasons: opinion piece or review with no usable original data (N = 18) (7-23), home and in-center patient data combined and reported in aggregate (N = 3) (24-26), and no patient-important outcomes reported (N = 2) (27,28). Twenty-two full-text articles were therefore included in this review (2)(3)(4)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). We also identified four ASN conference abstracts published between 2009 and 2011 (48)(49)(50)(51).…”
Section: Search and Study Selectionmentioning
confidence: 99%